(untitled) (Cardiovascular Journal, 2024)
Internal mammary artery is considered as the priceless conduit in all forms of surgical coronary artery revascularization. Harvesting technique of this artery, as a result, was widely debated. Harmonic scalpel is showing excellent result and some of the pioneers are using it for decades together around the globe disregarding our population. We are routinely using harmonic scalpel from the year 2022 and arranged this study to observe the outcomes in our population. Cardiovasc j 2024; 16(2): 78-80